MASA DEPAN HALAL LIFESTYLE DALAM MEMERANGI ISLAMOPHOBIA - Khoirul Umam; Hesti Maharani Dwi Rahayu; Radhiyatun Nisak (Qolamuna : Jurnal Studi Islam, 2024)
The study aims to provide an analytical study of halal lifestyles in the fight against Islamophobia. Islamophobia is a global phenomenon that results from the emergence of excessive fear related to everything about Islam. Islam is regarded as a hard religion, which is the source of terrorist acts and is ultimately seen as a serious threat to world peace. But Islam strongly advocates peace, which has the principle of freedom from fear, hunger, and insecurity. The methodology used in this study is a qualitative library research approach to literature related to halal lifestyle in combating Islamophobia, then analyzed empirically, and then concluded. So the results of this study show that a halal lifestyle has an important role in combating Islamophobia. With Muslims representing more than 24% of the world's population, they can give a complete picture of the Islamic face of the practice of the halal lifestyle. To show the world that the fitrah of a Muslim has a gentle, loving, and humble attitude. So, if we can show these values to the global community regularly, their hatred of Islam will be reduced. Keywords: Halal Lifestyle; Islamophobia